The effect of personal bankruptcy exemptions on investment in home equity - Corradin, Stefano; Gropp, Reint; Huizinga, Harry; Laeven, Luc (Journal of Financial Intermediation, 2016)
Homestead exemptions to personal bankruptcy allow households to retain their home equity up to a limit determined at the state level. Households that may experience bankruptcy thus have an incentive to bias their portfolios toward home equity. Using US household data for the period 1996–2006, we find that household demand for real estate is relatively high if the marginal investment in home equity is covered by the exemption. The home equity bias is more pronounced for younger and less healthy households that face more financial uncertainty and therefore have a higher ex ante probability of bankruptcy. These results suggest that homestead exemptions have an important bearing on the portfolio allocations of US households and the extent to which they insure against bad shocks.